Comparison of pleural responses of rats and hamsters to subchronic inhalation of refractory ceramic fibers. - Everitt, J I (1997)
In the present subchronic study, we compared pleural inflammation, visceral pleural collagen deposition, and visceral and parietal pleural mesothelial cell proliferation in rats and hamsters identically exposed to a kaolin-based refractory ceramic fiber, (RCF)-1 by nose-only inhalation exposure, and correlated the results to translocation of fibers to the pleural cavity. Fischer 344 rats and Syrian golden hamsters were exposed to 650 fibers/cc of RCF-1, for 4 hr/day, 5 days/week for 12 weeks. Following 4 and 12 weeks of exposure, and after a 12-week recovery period, pleural lavage fluid was analyzed for cytologic and biochemical evidence of inflammation. Visceral and parietal pleural mesothelial cell proliferation was assessed by immunocytochemical detection of bromodeoxyuridine incorporation. Pleural collagen was quantitated using morphometric analysis of lung sections stained with Sirius Red. Fiber-exposed rats and hamsters had qualitatively similar pleural inflammation at each time point. Mesothelial cell proliferation was more pronounced in hamsters than in rats at each time point and at each site. In both species, the mesothelial cell labeling index was highest in the parietal pleural mesothelial cells lining the surface of the diaphragm at each time point. Hamsters but not rats had significantly elevated collagen in the visceral pleura at the 12-week postexposure time point. Fibers were found in the pleural cavities of both species at each time point. These fibers were generally short and thin. These results suggest that mesothelial cell proliferation and fibroproliferative changes in the pleura of rodents following short-term inhalation exposure are associated with fiber translocation to the pleura and may be predictive of chronic pleural disease outcomes following long-term exposure.